'Don't forget the magic': the life and death of the British Film Institute's Museum of the Moving Image, London. Issue 4 (1st October 2016) - Herbert, Stephen
Abstract: From 1988 until its closure in 1999, the British Film Institute's groundbreaking Museum of the Moving Image (MOMI) on London's South Bank attracted several million visitors and critical acclaim. This account is authored by a member of the Curatorial team (1989–1996), and presented in three parts. First is a review of precedents and influences behind the project's development and critical reception, including a review of its collections and education. Next is a reflection on two temporary exhibitions, home movies, and the problem of updating exhibitions, given priorities and attendance figures. Finally, MOMI's closure and reinvention as MOMI 2 is considered in light of different approaches to media museums. The history of BFI's MOMI is set within broader challenges of time-based media as a museum subject, and the article includes observations on practical considerations and their impact on conceptual and academic concerns. The author privileges exhibitions and displays on which he had a curatorial role and those that accentuated early popular visual culture, although these constitute a small part of the museum's scope.